Modelling Imprecise Regions with Cognitive Perceptions and Georeferenced Data from the Web - Staples, Karsten (2019)
Place names are commonly communicated terms between individuals used to informally agree on a location. Although individuals can agree on the general whereabouts of a place such as the ‘city centre’, the extents of these regions vary based on factors that form perception. This study aims to compare perceptions of Nottingham city centre extents using responses from 52 pedestrians. These perceptions were modelled and compared to spatial extents derived from georeferenced data on the web. Various web sources portrayed contrast in their corresponding boundaries from the data based on each business plan. A detailed discussion follows the spatial data models and the focus of this research is explained. The influence of each business plan on the delineation of each boundary was investigated and identified.